The Duration and Safety of Osteoporosis Treatment Anabolic and Antiresorptive Therapy - Silverman, Stuart; Abrahamsen, Bo (Springer International Publishing : Imprint: Springer, 2016)
Providing a comprehensive review of short-and long-term adverse events of both antiresorptive and anabolic drugs, this practical guide updates the clinician on the pathophysiology of osteoporosis and the principles behind our present and future pharmaceuticals. Leading practitioners in the field examine all current literature and data regarding the duration and safety of these therapies, with recommendations for clinicians on decision-making and best practices for osteoporosis patients. An overview of the pathophysiology and epidemiology of osteoporosis and discussion of both anabolic and antiresorptive drugs is followed by fracture risk assessment and an examination of treatment failures. Next, a number of chapters are dedicated to the diagnosis, presentation and management of atypical femur fractures and osteonecrosis of the jaw (ONJ), each of which are significant patient concerns when using these osteoporosis treatments. The introduction and utilization of drug holidays is also discussed, as well as the long-term outlook for management of osteoporotic patients. Written and edited by experts in the field, The Duration and Safety of Osteoporosis Treatment is a balanced resource for researchers, practitioners and policy-makers alike for clinical decision-making and patient care.